Spatial metabolomics identifies localized chemical changes in heart tissue during chronic cardiac Chagas Disease. - Danya A Dean; Gautham Gautham; Jair L Siqueira-Neto; James H McKerrow; Pieter C Dorrestein; Laura-Isobel McCall (Public Library of Science (PLoS), 2021)
Chagas disease (CD), caused by the parasite Trypanosoma cruzi, is one of nineteen neglected tropical diseases. CD is a vector-borne disease transmitted by triatomines, but CD can also be transmitted through blood transfusions, organ transplants, T. cruzi-contaminated food and drinks, and congenital transmission. While endemic to the Americas, T. cruzi infects 7-8 million people worldwide and can induce severe cardiac symptoms including apical aneurysms, thromboembolisms and arrhythmias during the chronic stage of CD. However, these cardiac clinical manifestations and CD pathogenesis are not fully understood. Using spatial metabolomics (chemical cartography), we sought to understand the localized impact of chronic CD on the cardiac metabolome of mice infected with two divergent T. cruzi strains. Our data showed chemical differences in localized cardiac regions upon chronic T. cruzi infection, indicating that parasite infection changes the host metabolome at specific sites in chronic CD. These sites were distinct from the sites of highest parasite burden. In addition, we identified acylcarnitines and glycerophosphocholines as discriminatory chemical families within each heart region, comparing infected and uninfected samples. Overall, our study indicated global and positional metabolic differences common to infection with different T. cruzi strains and identified select infection-modulated pathways. These results provide further insight into CD pathogenesis and demonstrate the advantage of a systematic spatial perspective to understand infectious disease tropism.